Relação entre volume e volatilidade no mercado acionário brasileiro - Macret, Deborah Zilberman (2018)
This work seeks to identify patterns in intraday volatility in the Brazilian stock market and then outline a trading strategy based on them. In some studies, the behavior of volatility is associated with the behavior of the volume traded. This, in turn, follows the ’U’ format during the day - larger negotiations in the initial and final hours, being relatively smaller in the intervening period. Based on the analysis of shares of the Ibovespa portfolio, we conclude that the Brazilian market also follows this behavior. The strategy chosen, then, is to sell volatility early in the day and buy it in the intervening period. For this, we use strangles.